Changes in patellar tendon complaints and shear wave velocity patterns among competitive alpine skiers during a 4-year post-growth spurt follow-up - Hanimann, J.; Fitze, D. P.; Götschi, T.; Fröhlich, S.; Frey, W. O.; de Bruin, E. D.; Sutter, R.; Spörri, J. (Frontiers in Physiology, 2024)
Patellar tendon (PT) complaints are frequent in competitive alpine skiers and such complaints are characterized by a long-lasting affection. Since PTs are subject to maturation up to 1-2 years after growth spurt, this early career stage may be decisive for the further course of complaints. The aim of this study was to investigate the evolution of PT complaints and shear wave velocity patterns among competitive alpine skiers during a 4-year post-growth spurt follow-up. The PT complaints and SWV patterns of forty-seven skiers were analysed at baseline (i.e., immediately after their peak height growth at 13-15 years of age) and were re-analysed at 4-year follow-up. The PTs were scanned via three-dimensional SWE. Symptomatic skiers were identified based on pain sensation under loading and pressure-induced pain around the PT. The prevalence of PT complaints decreased from 29.8% at baseline to 12.8% at follow-up (Pearson`s x2 = 9.429; p = 0.002). SWV decreased from the baseline assessment to the follow-up in the proximal and distal regions (p < 0.05). SWV coefficient of variation (CV) in the distal and mid-portion regions was greater at baseline than at follow-up (p < 0.05). At the follow-up assessment, compared to "healthy" skiers, "healed" skiers who recovered from PT complaints had lower SWVs in the proximal region (p = 0.020) and greater SWV CVs in the proximal region (p = 0.028). Moreover, symptomatic skiers had significantly greater SWV CVs in the mid-portion region than did "healthy" subjects with no history of PT complaints (p = 0.020). The average SWV was negatively correlated with the SWV (proximal: r = -0.74, p < 0.001; mid-portion: r = -0.37 p = 0.011; and distal: r = -0.58, p < 0.001). The occurrence of PT complaints decreased over a 4-year post-growth spurt follow-up. "Healed" skiers who were symptomatic at baseline had an even greater average decrease in the proximal and mid-portion SWV than "healthy" skiers with no history of PT complaints. This may lead to the hypothesis that PT complaints in adolescent skiers are not self-eliminating towards the end of adolescence, as at least structural irregularities appear to persist for several years after the onset of initial symptoms. Furthermore, "healed" and symptomatic tendons exhibited increased SWV variability, supporting the hypothesis that SWV CV may provide additional valuable information on the mechanical properties of PTs affected by overuse-related complaints.